KEPEMIMPINAN SPIRITUAL (SPIRITUAL LEADERSHIP) GURU SEKOLAH DASAR DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK - Hermanto Halil (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2020)
As a leader will have a big influence on those they lead. Teacher leadership isone of the factors that influence the character building of students,considering that in Javanese philosophy, the teacher is a person who isimitated and is the spearhead in the class who is face to face with students.The teacher accompanies students so that he will be the next leader. Theleadership effectiveness of an organization cannot be separated from spiritualvalues. Therefore, it is important to instill spiritual values in the teacher asa leader in the class. Fulfilling spiritual needs in the classroom will have apositive effect on the character building of students and can be used as afoundation in the application of spiritual leadership.